USING MANIPULATIVES IN ETH-COOPERATIVE LEARNING TO ENHACE MATHEMATICAL LEARNING OUTCOMES - Eyus Sudihartinih (Universitas Brawijaya, 2020)
This study aims to obtain an overview of the improvement in student mathematics learning outcomes using manipulatives with Cooperative Learning Everyone is a Teacher Here (ETH- cooperative learning) and students who learn to use manipulatives with conventional learning. The research design used was quasi-experiment with the type of pretest posttest control group design with a population of all first-level students who were studying matriculation at one of the STIKES in Indonesia. The number of samples of two classes was selected by purposive sampling, with the number of control class students being 38 people and the experimental class being 44 people. Class A as a control class gets conventional learning using manipulatives. Class B as an experimental class receives learning by using manipulatives through ETH-cooperative learning. The result is an increase in mathematics learning outcomes of students who learn to use manipulatives with ETH-cooperative learning higher than students who learn to use conventional manipulatives.